(untitled) (The International Research Journal of Management Science, 2024)
Purpose: In today’s competitive marketplace, brand awareness is crucial for a company’s success. It reflects the degree to which consumers recognize a brand’s unique characteristics and image, influencing customer acquisition, loyalty, and market presence. This study aims to identify factors affecting the brand awareness of Goldstar shoes in Nepal. Design/Methodology/Approach: Using a descriptive and causal-comparative research design, the study targeted 204 Goldstar customers from different occupations in Kathmandu Valley, selected through convenience sampling. Data was collected via a structured questionnaire with a five-point Likert scale and analyzed using correlation and regression techniques. Findings: The study found a positive relationship between social media marketing, electronic word-of-mouth (eWOM), and sponsorships with brand awareness. These factors significantly influence Goldstar’s brand awarenss. Conclusion: Social media marketing, eWOM, and sponsorships are key drivers of brand awareness for Goldstar shoes. Investing in dynamic social media campaigns, encouraging online reviews, and leveraging strategic sponsorships can enhance brand visibility and market presence. An integrated approach combining these strategies is recommended. Limitations/Implications: The study utilized only three independent variables: social media marketing, electronic word-of-mouth, and sponsorship, to examine their impact on brand awareness of Goldstar shoes within Kathmandu Valley. Hence, future researchers can study other factors impacting brand awareness of other brands in other cities with a larger sample size and with new analytical tools. Originality/Value: This study applies the AIDAS Model (Lewis, 1898) to understand customer buying behavior for Goldstar shoes.